Resource loss moderates the association between child abuse and current PTSD symptoms among women in primary-care settings - Costa, Eleonora C. V. (2019)
This study examined if abuse during childhood, rape in adulthood, and loss of resources predict a woman's probability of reporting symptoms of posttraumatic stress disorder (PTSD), and whether resource loss moderates the association between reporting childhood abuse and PTSD symptoms. The sample included 767 women and was collected in publicly funded primary-care settings. Women who reported having been abused during childhood also reported more resource loss, more acute PTSD symptoms, and having suffered more adult rape than those who reported no childhood abuse. Hierarchical logistic regression yielded a two-variable additive model in which child abuse and adult rape predict the probability of reporting or not any PTSD symptoms, explaining 59.7% of the variance. Women abused as children were 1 to 2 times more likely to report PTSD symptoms, with sexual abuse during childhood contributing most strongly to this result. Similarly, women reporting adult rape were almost twice as likely to report symptoms of PTSD as those not reporting it. Resource loss was unexpectedly not among the predictors but a moderation analysis showed that such loss moderated the association between child abuse and current PTSD symptoms, with resource loss increasing the number and severity of PTSD symptoms in women who also reported childhood abuse. The findings highlight the importance of early assessment and intervention in providing mental health care to abused, neglected, and impoverished women to help them prevent and reverse resource loss and revictimization.